Increased glucocorticoid concentrations in early life cause mitochondrial inefficiency and short telomeres - Casagrande Stefania; Stier Antoine; Monaghan Pat; Loveland Jasmine L.; Boner Winifred; Lupi Sara; Trevisi Rachele; Hau Michaela (COMPANY BIOLOGISTS LTD, 2025)
Telomeres are DNA structures that protect chromosome ends. However, telomeres shorten during cell replication and at critically low lengths can reduce cell replicative potential, induce cell senescence and decrease fitness. Stress exposure, which elevates glucocorticoid hormone concentrations, can exacerbate telomere attrition. This phenomenon has been attributed to increased oxidative stress generated by glucocorticoids ('oxidative stress hypothesis'). We recently suggested that glucocorticoids could increase telomere attrition during stressful periods by reducing the resources available for telomere maintenance through changes in the metabolic machinery ('metabolic telomere attrition hypothesis'). Here, we tested whether experimental increases in glucocorticoid levels affected telomere length and mitochondrial function in wild great tit (Parus major) nestlings during the energy-demanding early growth period. We monitored resulting corticosterone (Cort) concentrations in plasma and red blood cells, telomere lengths and mitochondrial metabolism (metabolic rate, proton leak, oxidative phosphorylation, maximal mitochondrial capacity and mitochondrial inefficiency). We assessed oxidative damage caused by reactive oxygen species (ROS) metabolites as well as the total non-enzymatic antioxidant protection in plasma. Compared with control nestlings, Cort-nestlings had higher baseline corticosterone, shorter telomeres and higher mitochondrial metabolic rate. Importantly, Cort-nestlings showed increased mitochondrial proton leak, leading to a decreased ATP production efficiency. Treatment groups did not differ in oxidative damage or antioxidants. Hence, glucocorticoid-induced telomere attrition is associated with changes in mitochondrial metabolism, but not with ROS production. These findings support the hypothesis that shortening of telomere length during stressful periods is mediated by glucocorticoids through metabolic rearrangements.